2023
DOI: 10.1002/cam4.6057
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease increases the risk of hepatobiliary pancreatic cancer: A two‐sample Mendelian randomization analysis of European and East Asian populations

Abstract: Background Both inflammatory bowel disease (IBD) and hepato‐pancreato‐biliary cancers (HPBC) have been established to cause a huge socioeconomic burden. Epidemiological studies have revealed a close association between IBD and HPBC. Methods Herein, we utilized inverse‐variance weighting to conduct a two‐sample Mendelian randomization analysis. We sought to investigate the link between various subtypes of IBD and HPBC. To ensure the accuracy and consistency of our findings, we conducted heterogeneity tests, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…This approach allows for the effective avoidance of confounding agents, which can be elusive to control for in observational studies. 15 Since alleles that affect genetic variants are distributed randomly to offspring at gestation, regardless of environmental and other uncharted confounders, MR analyses are analogous to natural randomized controlled trials. 16 Such analyses permit the assessment of causality between exposures and outcomes at the genetic level while ruling out the likelihood of reverse causality.…”
Section: Introductionmentioning
confidence: 99%
“…This approach allows for the effective avoidance of confounding agents, which can be elusive to control for in observational studies. 15 Since alleles that affect genetic variants are distributed randomly to offspring at gestation, regardless of environmental and other uncharted confounders, MR analyses are analogous to natural randomized controlled trials. 16 Such analyses permit the assessment of causality between exposures and outcomes at the genetic level while ruling out the likelihood of reverse causality.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, genetic factors that predispose individuals to IBD might also be linked to an increased risk of pancreatic cancer 36,37 . Our study revealed that IBD is associated with a raised risk of pancreatic cancer based on MR studies 28,29 . Exacerbating inflammation in the pancreas caused by shared genetic factors may contribute to the development of pancreatic cancer.…”
Section: Discussionmentioning
confidence: 64%
“…For this systematic review and meta‐analysis, we screened 5201 citations from the initial database search. After excluding 5188 publications because of duplication or unsuitability, we identified 13 eligible articles, including 11 cohort studies regarding the first study aim 5,8–11,22–27 and two studies concerning the second study aim 28,29 . The search strategy and process for study selection are illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also manifests extraintestinally, primarily affecting areas such as the eyes, skin, joints, and biliary system [4]. The systemic chronic in ammation induced by IBD increases the risk of developing other long-term conditions (LTCs), including cardiovascular diseases [5], diabetes [6], cancers [7,8], liver diseases [9], respiratory disorders [10], and musculoskeletal diseases [11]. The systemic chronic in ammation caused by IBD disrupts the balance of neurotransmitter secretion involved in emotional regulation and cognitive function, potentially leading to the occurrence of depression and anxiety [12,13].…”
Section: Introductionmentioning
confidence: 99%